THE PORTRAYAL OF ECONOMIC ORIGINAL PICTURE FROM THE NOVELS OF MR LAHARY: SIGNIFICANT REVIEW OF BODOS, DWELERS OF ASSAM - Baro, Dwipen (International Journal of Research -GRANTHAALAYAH, 2019)
Bodo literature is a developing literature after the Assamese literature in Assam. Monoranjan Lahary is a popular and prominent writer. In the mentioned topic, it will be criticized concerning some economic earning methods and systems inherently followed by the Bodos, portrayed by Monoranjan Lahary in his novels. He has used different kind of original habits of the Bodos, which are not alike to the contemporary dwellers of Assam. In his novel, he reflects the genuine technique or habits of the Bodo people to earn the money. He uses concrete idea in his novels having used the genuine picture. The readers can enjoy and earn knowledge so much, as they have required from the novel of Lahary, about the Bodos. The works and the habits always influenced to other communities to follow the same. This paper attempts to show the nature of living of the Bodos, that the Bodos do physical hard labor, where there was no impact of modernism. In the discussion, the dialogues and the quotations are given in the same language i.e. Bodo, as used in the novels by the novelist Monoranjan Lahary.